The Influence Of Lifestyle And Risk Perception On The Intention To Use Paylater, Moderated By Trust - Persada, Ni Kadek Gita Sri; Permadi, Lalu Adi (UNIVED Press, 2026)
The rapid development of Paylater services in Indonesia, as part of the digital transformation and growth of e-commerce, has facilitated transactions without the need for credit cards, yet it raises concerns about financial and social risks that influence user intentions. This study's objective is to establish the effects of lifestyle and risk perception on the aim to use Pay Later services, with assign as a moderating variable. A quantitative technique was employed with data collected by online questionnaires and examined by Partial Least Squares (PLS). The outcomes indicate that lifestyle has a significant positive influence on usage intention, while risk perception has a significant negative influence, but trust does not significantly moderate these relationships. In conclusion, psychological and social factors are crucial in decisions regarding Paylater usage, making targeted marketing strategies and risk education key to increasing adoption of these services.